ظاهرة العولمة –تجلياتها وتأثيراتها- - ربيحة, نبار (جامعة الوادي - University of Eloued, 2018)
يعد اصطلاح العولمة من احدث المفردات اللغوية و التي شاع استخدامها على نطاق واسع ،وتم تداولها بسرعة خلال سنوات قليلة وذلك لارتباطها بالتغيرات السريعة التي شهدها النظام العالمي في مختلف مناحي الحياة السياسية والاقتصادية والاجتماعية والثقافية والتكنولوجية والعسكرية ، وقد كان للعولمة تأثيرا كبيرا في المجتمعات نظرا للتدفق المعلوماتي السريع والتطورات العلمية والتكنولوجية التي شهدتها جميع الأصعدة ،وكذلك تنوع أبعادها ومظاهرها،وقد استطاعت العولمة أن تتعدى نطاق القوميات وتتجاوز حدود الدول والأقاليم ، كما أثرت في حياة الناس بشكل رهيب وبنسب مختلفة بغض النظر عن العرق أو اللغة أو البلد.The term "globalization" is one of the most modern and widely used vocabulary in the world. It has been widely circulated in a few years because of the rapid changes in the world order in various aspects of political, economic, social, cultural, technological and military life. Globalization has had a significant impact on societies Societies because given the rapid information flow and scientific and technological developments at all levels, as well as the diversity of its dimensions and manifestations, it has been able to transcend the scope of nationalities and beyond the borders of States and territories, and also affected the lives of people in a terrible and with different proportions Regardless of race, language or country.
The phenomenon of globalization - its manifestations and effects -
مقال
Keywords: العولمة; globalization.